Pengaruh Kompensasi dan E-Absensi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Pendidikan Dan Kebudayaan Kota Padang - Yulia, Diana; Candana, Dori Mitra; Afuan, M. (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the influence of compensation and e-attendance on employee performance, with job satisfaction as an intervening variable at the Padang City Education and Culture Office. Data collection was conducted through a survey and questionnaire distribution, with a sample of 69 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of compensation on job satisfaction. There was a significant effect of e-attendance on job satisfaction. There was a significant effect of compensation on employee performance. There was a significant effect of e-attendance on employee performance. There was a significant effect of job satisfaction on employee performance. There was a significant effect of compensation on employee performance through job satisfaction. There was a significant effect of e-attendance on employee performance through job satisfaction.